2015
DOI: 10.1115/1.4030809
|View full text |Cite
|
Sign up to set email alerts
|

Bleed-Induced Distortion in Axial Compressors

Abstract: In this paper, the influence of nonuniform bleed extraction on the stability of an axial flow compressor is quantified. Nonuniformity can be caused by several geometric factors (for example, plenum chamber size or number of off-take ducts), and a range of configurations is examined experimentally in a single stage compressor. It is shown that nonuniform bleed leads to a circumferential distribution of flow coefficient and swirl angle at inlet to the downstream stage. The resultant distribution of rotor inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…Aerodynamic studies have shown that the impact of bleed can be beneficial in reducing the blockage effect that is dominant in the downstream stage of the compressor. This can improve the compressor stability when extracted uniformly/circumferentially as demonstrated by Grimshaw et al 13 that shows an improvement in the stall inception when the flow is extracted in front of the rotor. In a similar but CFD study, Gou et al 14 show that the extraction or bleeding brings about an increase in the stage isentropic efficiency, deterioration in the transport of the tip leakage flow to the rotor blade pressure side and a reduction in the blockage.…”
Section: Methodology and Engine Specificationmentioning
confidence: 87%
See 1 more Smart Citation
“…Aerodynamic studies have shown that the impact of bleed can be beneficial in reducing the blockage effect that is dominant in the downstream stage of the compressor. This can improve the compressor stability when extracted uniformly/circumferentially as demonstrated by Grimshaw et al 13 that shows an improvement in the stall inception when the flow is extracted in front of the rotor. In a similar but CFD study, Gou et al 14 show that the extraction or bleeding brings about an increase in the stage isentropic efficiency, deterioration in the transport of the tip leakage flow to the rotor blade pressure side and a reduction in the blockage.…”
Section: Methodology and Engine Specificationmentioning
confidence: 87%
“…This can improve the compressor stability when extracted uniformly/circumferentially as demonstrated by Grimshaw et al. 13 that shows an improvement in the stall inception when the flow is extracted in front of the rotor. In a similar but CFD study, Gou et al.…”
Section: Flow Extraction – Chargingmentioning
confidence: 87%
“…In the passive flow control methods such as casing treatment (Houghton et al 2012;Sakuma et al 2014;Du et al 2016), blade tip winglet (Han et al 2014(Han et al , 2016 and blade tip modifications (Gourdain et al 2009;Ma et al 2012;Jung et al 2016), the geometrical change always works among the whole operating range and it may lead to a decrease of compressor performance near the design condition. For the active flow control techniques such as plasma actuation (Saddoughi et al 2015;Ashrafi et al 2016), tip injection (Li et al 2015;Grosvenor et al 2015;Khaleghi et al 2016) and casing aspiration (Lee et al 1990;Gmelin et al 2011;Grimshaw et al 2015), however, it can act on the flow fields flexibly either all the time or only when it is needed. As one of the effective active flow control methods, the suction technique attracts the attention from an increasing number of researchers to improve the flow fields in compressors.…”
Section: Introductionmentioning
confidence: 99%
“…So far the studies about suction mainly concentrate on the control of the boundary layer separation on the blade SS (Song et al 2006;Guo et al 2010;Shi et al 2015b) or the three-dimensional (3D) separation in the hub corner (Sachdeva et al 2011;Pönick et al 2013;Guo et al 2008;Marsan et al 2015). Apart from some researches about the effects of bleeding system on the compressor performance (Leishman et al 2007a(Leishman et al , 2007b(Leishman et al , 2007cGrimshaw et al 2015Grimshaw et al , 2016, there are only several investigations of suction technique on the control of TLF to improve the compressor performance and stability (Gümmer et al 2008;Dobrzynski et al 2008;Shi et al 2015a). It is found that the flow fields in the tip region and operating range can be improved by the suction on the casing.…”
Section: Introductionmentioning
confidence: 99%
“…While the active flow control can be imposed on the flow fields flexibly either all the time or only when the compressor’s operating point moves dangerously close to the stall line, such as plasma actuation, 3133 tip injection, 3438 and aspiration/suction techniques. 3944 At present, the researches about aspiration mainly focus on the control of the boundary layer separation on blade SS or the 3D separation in the hub corner, 4550 and the results show that the performance of compressor cascade can be improved significantly by applying the suction method.…”
Section: Introductionmentioning
confidence: 99%